25 Weaning of VA ECMO: our experience. (9th April 2018) - Chan, Kai-Man
Abstract : There is a lack of consensus on the timing of decannulation for venoarterial extracorporeal membrane oxygenation (VA-ECMO). Premature decannulation results in haemodynamic deterioration and urgent recannulation, while prolonging unneeded ECMO support leads to significant morbidity and mortality. VA-ECMO weaning usually consists of serial decrements until an idling flow of 0.5–1.0 L/min is achieved, supported by echocardiographic and haemodynamic assessment. Even with this minimal idling flow, right ventricular (RV) preload is reduced and, hence, right heart function is not fully tested under adequate loading conditions. Gas exchange is only partially assessed in the presence of sweep gas flow. Trial off by using an arteriovenous bridge within the circuit allows recirculation and temporary separation of ECMO from the patient. However, it requires intermittent circuit clamping and carries a significant risk of circuit thrombosis. In 2013 Westrope, et al . reported a technique for VA-ECMO weaning, pump controlled retrograde trial off (PCRTO), in neonates with respiratory failure. Retrograde flow ensures adequate RV filling and proper assessment of RV function. As sweep gas is turned off during PCRTO, native gas exchange is fully assessed. We share our experience in using PCRTO as an assessment tool in adult VA-ECMO weaning. Reference: . Westrope, et al .